Factors Impacting Nutritional Status in Infants with Single Ventricle Physiology - Mark Gormley; Emily Behling; Rebecca Frees; Kavisha Shah; Stacie Knutson; Nathan Rodgers; Melissa S. Engel; Shanti Narasimhan (Journal of Pediatric Health And Nutrition, 2025)
Infants with single ventricle (SV) physiology are at increased risk of undernutrition, which can contribute to adverse outcomes. This is a retrospective case series examining factors associated with undernutrition in patients with SV physiology at one year of age. It includes 56 infants from a single institution who underwent SV palliation between 2003 and 2023. Undernutrition was defined as a weight-for-length z-score (WLZ) below -1, based on World Health Organization (WHO) normative data. Independent variables included surgical interventions, cardiorespiratory factors, and nutritional interventions. Associations between these variables and nutritional status were assessed using Fisher’s exact test. At one year, a total of nine infants (16%) were undernourished. Undernutrition rates significantly declined after 2013 (p=0.02), demonstrating improvements in nutritional outcomes over our study period. Those who used supplemental oxygen or pulmonary medications were undernourished at lower rates. While this difference was not statistically significant, the number of undernourished patients in the cohort may have limited the study’s power. Our findings suggest that early respiratory interventions may provide nutritional benefits in infants with SV physiology.
Keywords: Single ventricle